LogTechs in Brazil: how logistics start-ups are applying Industry 4.0 technologies: a multi-case study - Ojeda Larrosa, Natalia María (2021)
Purpose – This research aims to explore the Industry 4.0 technologies that are being adopted by logistics start-ups in Brazil, which are also called LogTechs. Design/methodology/approach – It is qualitative research, analyzed through case studies. To collect the empirical data, interviews were carried out with the founders or representatives of the start-ups. A multi-case study enables the exploration of the different existing tools to optimize logistics operations and the analysis of specific cases that are successful in Brazil. Findings – The research provides meaningful insights about Industry 4.0 tools to optimize logistics processes and how LogTechs companies in Brazil apply them. Also, describes the challenges faced by Logtechs in Brazil. Originality/value – Beyond explaining the uses and benefits of logistics 4.0 technologies, they are analyzed in successful cases of Brazilian Logtech companies.